3x+2x+7=-41

Simple and best practice solution for 3x+2x+7=-41 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+2x+7=-41 equation:


Simplifying
3x + 2x + 7 = -41

Reorder the terms:
7 + 3x + 2x = -41

Combine like terms: 3x + 2x = 5x
7 + 5x = -41

Solving
7 + 5x = -41

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 5x = -41 + -7

Combine like terms: 7 + -7 = 0
0 + 5x = -41 + -7
5x = -41 + -7

Combine like terms: -41 + -7 = -48
5x = -48

Divide each side by '5'.
x = -9.6

Simplifying
x = -9.6

See similar equations:

| -27=2c-7c-6c | | 3x+1=3x-8 | | 15x+45=120 | | 6(2t-5)=60-6t | | 1/2=3/3 | | 3.75x=21 | | 5x+4x=7 | | 2x-10y=10 | | k=25 | | 16w^2-70w+49=0 | | t+9-3.2=3 | | 8c-72=8c-72 | | 5t+16=11t+4 | | 8x-2=20x+4 | | -6x+4y=-16 | | t+7=-t+5 | | 3n(n-5)-7(3n+9)= | | 16+32x=40x | | 3.89-13=1.4+5 | | 9x^2-2x-11=0 | | 9(12x+6)= | | 3x+4-x=53 | | 2x(x+9)-7X= | | 0.2(0.23-5x)=-0.9x | | -144=18n | | 6(n+3)=12-.12n | | X^3-5x^2-16x+80=0 | | 5x^2-21x+16=0 | | -6(9x-7)=420 | | 1.4z-42=2.8 | | 5n^2+32n-64=0 | | -50+6a=-10(a-1) |

Equations solver categories